The Relationship Between the Impact of the Covid-19 Pandemic and Adolescent - Linda Dwi Novial; Putri Annisa; Mega Surya; Nurhayati; Tarmizi (Promotion and Prevention in Mental Health Journal, 2025)
COVID-19 is a non-natural disaster that can have an impact on mental and psychosocial health and can be experienced by all groups, especially adolescents. Adolescence is a transitional stage from childhood to adulthood where adolescents experience many psychological, social, and biological changes at this stage. In addition, adolescence is a vulnerable age stage and is very at risk of emotional and behavioral problems because it is in the development stage. The COVID-19 pandemic has had an impact on increasing anxiety problems, sleep disorders, social isolation, depression, and stress experienced by adolescents. This is because the COVID-19 pandemic has forced adolescents to limit social interactions with friends of the same age, causing adolescents to interact a lot online, and adolescents have to be sent home to avoid the spread of COVID-19, limited activities outside the home, frustration, boredom, fear of infection, and inaccurate information about COVID-19. Based on the description above, researchers want to see the actual phenomenon to obtain data related to changes in adolescents' mental health during the COVID-19 pandemic, especially in Samarinda.